معمر بن راشد الأزدي ودوره في تاريخ تطور الحديث بعد تدوينه كتابا "الجامع" والمغازي" أنموذجا - Muhid Muhid; Muhammad Ilyas; Andris Nurita (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
The post-codification of Hadith is a very important era in the history of the development of hadith; in that era there appeared a scholar named Ma'mar ibn Rāshid who was instrumental in the perfection of codification, this is very important to be further researched because of the importance of his role and work which is not widely known to Muslims or even disputed its veracity. This study talks about the role of Imam Ma'mar ibn Rāsyid in the development of the Hadith of the Prophet after it was written in the era of Imam al-Zuhrī. His research focused on two books he wrote, al-Jāmi' and al-Maghāzī. This research is a literature study with qualitative methods with descriptive and analytical approaches accompanied by comparative studies. The most notable result of the study is the validity of the al-Jāmi' books and al-Maghāzī books which are the original works of Imam Ma'mar bin Rāsyid, and that imam Ma'mar had a major role in the development of the Prophet's Hadith which is summarized in the following: First: Innovation and creativity in the bookkeeping of hadith thematically. Second: Diversified in authorship where he has written al-Jāmi' books which a compilation of the Hadith of the Prophet al-Maghāzī in the field of the history of the Prophet, whose main purpose is to ensure the validity of the historical history, and the book of interpretation of the Qur'an. Third: Writers and scholars have paid so much attention to the work of Imam Ma'mar ibn Rāshid that they quote so much from him. Fourth: The Book of al-Jāmi' is among the first complications of hadith printed to date, earlier than Muwatṭa' Mālik.